Quercetin improves neurobehavioral performance through restoration of brain antioxidant status and Acetylcholinesterase activity in Manganese-treated rats (2017)
The present study investigated the neuroprotective mechanism of quercetin by assessing the biochemical and behavioral characteristics in rats sub-chronically treated with manganese alone at 15 mg/kg body weight or orally co-treated with quercetin at 10 and 20 mg/kg body weight for 45 consecutive days. Locomotor behavior was monitored using video-tracking software during a 10-min trial in a novel environment whereas the brain regions namely the hypothalamus, cerebrum and cerebellum of the rats were processed for biochemical analyses. Results indicated that co-treatment with quercetin significantly (p < 0.05) prevented manganese-induced locomotor and motor deficits specifically the decrease in total distance travelled, total body rotation, maximum speed, absolute turn angle as well as the increase in time of immobility and grooming. The improvement in the neurobehavioral performance of manganese-treated rats following quercetin co-treatment was confirmed by track and occupancy plot analyses. Moreover, quercetin assuaged manganese-induced decrease in antioxidant enzymes activities and the increase in acetylcholinesterase activity, hydrogen peroxide generation and lipid peroxidation levels in the hypothalamus, cerebrum and cerebellum of the rats. Taken together, quercetin mechanisms of ameliorating manganese-induced neurotoxicity is associated with restoration of acetylcholinesterase activity, augmentation of redox status and inhibition of lipid peroxidation in brain of rats.